Does relaxing household credit constraints hurt small business lending? Evidence from a policy change in Texas - Bahadir, Berrak; Gumus, Inci; Schaffer, Matthew (Journal of Corporate Finance, 2024)
This paper studies the relationship between household credit and small business loans using the 1997 liberalization of home equity lending in Texas. First, we build a closed economy general equilibrium model that examines two opposing channels: a negative crowding out effect and a positive collateral effect. Our analysis shows that, following a household credit expansion, the crowding out effect dominates and leads to an overall decline in firm borrowing. We test this result empirically by exploiting the liberalization of home equity loans in Texas. The exogenous increase in household credit brought on by the liberalization results in a crowding out of business lending, as small business loan growth declines by roughly 20 percentage points. This negative effect is dampened in counties that experienced stronger house price growth, providing evidence of a subsidiary collateral effect. We further explore the bank-level factors that could influence the strength of the crowding out effect and find that the effect is weaker for banks with easier access to funding and a specialization in business lending.